1993
DOI: 10.1111/j.1475-097x.1993.tb00381.x
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine reduces blood pressure and forearm vascular resistance and increases forearm blood flow in healthy young adults

Abstract: The effects of chloroquine on resting blood pressure, forearm blood flow (FBF), and forearm vascular resistance (FVR) and on the responses to cold stimulation were studied in healthy young adults. Chloroquine sulphate (800 mg) reduced systolic pressure and increased FBF (P < 0.05) but had no effect on resting FVR. Cold immersion increased systolic pressure (from 108.8 +/- 1.7 mmHg to 127.8 +/- 6.9 mmHg; P < 0.05) diastolic pressure (from 73.4 +/- 2.7 to 95.2 +/- 6.2 mmHg; P < 0.01) and FVR (from 5.9 +/- 0.9 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 6 publications
1
14
0
Order By: Relevance
“…In accordance with our lowered blood pressure in adult SHR, toxicity studies with chloroquine have observed a reduction in blood pressure in humans and rats [34, 35], as well as the magnitude of pressor responses to cold immersion in humans [34]. However, the mechanisms underlying these reductions were not elucidated from these studies.…”
Section: Discussionsupporting
confidence: 73%
“…In accordance with our lowered blood pressure in adult SHR, toxicity studies with chloroquine have observed a reduction in blood pressure in humans and rats [34, 35], as well as the magnitude of pressor responses to cold immersion in humans [34]. However, the mechanisms underlying these reductions were not elucidated from these studies.…”
Section: Discussionsupporting
confidence: 73%
“…They were also associated with lower blood pressure. While the hypotensive effects of antimalarials are well known [24,25], these findings were mainly with chloroquine used to treat malaria and not with hydroxychloroquine in a rheumatological setting. Thus, our findings suggesting that hydroxychloroquine is associated with lower blood pressure in a rheumatological setting, is a novel finding.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of chloroquine in the therapy of porphyria cutanea tarda (69) could be mediated by NO, which has been reported to inhibit heme synthesis (2). On the other hand, an increased NO production may account for some side effects of chloroquine, mainly observed after treatment with high doses of drug or during parenteral administration: inhibition of platelet aggregation (70), transient hypotension (71), reduced forearm vascular resistance (72), in vivo vasodilation (73), mutagenic effects (74), and neuropathies (75). If so, NOS inhibitors could be associated to high dosage chloroquine treatment to prevent the onset of several toxic effects of the drug.…”
Section: Discussionmentioning
confidence: 99%